The Changing Faces of Catholicism: National Processes and Central, Local and Institutional Strategies, Volume 9: The Changing Faces of Catholicism. - Solange Lefebvre; Alfonso Pérèz-Agote Poveda (Editors) (Annual Review of the Sociology of Religion, 2018)
Catholicism is generally over-institutionalized and over-centralized in comparison to other religions. However, it finds itself in an increasingly interrelated and globalized world and is therefore immersed in a great plurality of social realities. The Changing Faces of Catholicism assembles an international cast of contributors to explore the consequent decline of powerful Catholic organisations as well as to address the responses and resistance efforts that specific countries have taken to counteract the secularization crisis in both Europe and the Americas. It reveals some of the strategies of the Catholic Church as a whole, and of the Vatican centre in particular, to address problems of the global era through the dissemination of spiritually progressive writing, World Youth Days, and the transformation of Catholic education to become a forum for intercultural and interreligious dialogue. The volume also reflects on the adaptation of Catholic institutions and missions as sponsored by religious communities and monastic orders.